KONSTRUBUSI GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KUALITAS AKHLAK SISWA SMA NEGERI 1 PALOPO - Naidin Syam (Institut Agama Islam Negeri Palopo, 2018)
This research is about the contribution of Islamic education teachers in improving the moral quality of students at SMA Negeri 1 Palopo. This research is qualitative research using a philosophical and pedagogic approach. The informants consisted of the principal, the representative of the school, and the teachers. Data collection is done by observation, interview and documentation techniques. Data analysis by means of data reduction, data presentation, conclusions and data verification. For the results of the study, there are: 1) The contribution of Islamic education teachers in improving the moral quality of students at SMA Negeri 1 Palopo achieves optimal results. Based on the observations through interviews, it can e concluded that theteaching ability of Islamic education teachers is good, inviting students to do commendable activities, preventing the students from being blamed, and forming religious attitudes with the pattern of fostering religious life of students. Supported by several factors such as the involvement of school teachers, school programs, and the ability of school principals to empower the available resaources in schools. 2) There are several influential obstacles, namely: the lack of parents’ education and the negative impact of advancement of science and technology. The implications of this study are expected to increase the students’ moral quality into school priority, optimization of intensive coaching, principals, vice principals and teachers conduct continuous evaluations, so that the shortcomings and obstacles can be improved in the next moral development.